Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0148607115625220
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Loading Dose of Vitamin D for Treatment of Vitamin D Deficiency in Patients With Intestinal Failure

Abstract: Vitamin D deficiency is common in patients with intestinal failure and short bowel syndrome who have been weaned of parenteral nutrition. Dietary supplementation with vitamin D is necessary to correct this deficiency. In certain cases, routine supplementation strategy may be ineffective. We report 3 cases of vitamin D deficiency in patients with intestinal failure who showed improvement in serum 25-hydroxyvitamin D levels after supplementation with a loading dose of 20,000-40,000 IU vitamin D provided weekly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Previously, 10%–20% of patients with intestinal failure were reported to require daily oral vitamin D 3 at a dosage of 5,000–6,000 IU. Additionally, a smaller number of patients still do not respond to a high amount of vitamin D 3 [ 11 ]. Grenade et al [ 11 ] reported that a loading dosage of 20,000–40,000 IU of vitamin D 3 once a week, with a daily maintenance dosage of 4,000–6,000 IU/day on the remaining 6 days, has shown efficiency in improving the vitamin D level of 3 patients with intestinal failure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, 10%–20% of patients with intestinal failure were reported to require daily oral vitamin D 3 at a dosage of 5,000–6,000 IU. Additionally, a smaller number of patients still do not respond to a high amount of vitamin D 3 [ 11 ]. Grenade et al [ 11 ] reported that a loading dosage of 20,000–40,000 IU of vitamin D 3 once a week, with a daily maintenance dosage of 4,000–6,000 IU/day on the remaining 6 days, has shown efficiency in improving the vitamin D level of 3 patients with intestinal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a smaller number of patients still do not respond to a high amount of vitamin D 3 [ 11 ]. Grenade et al [ 11 ] reported that a loading dosage of 20,000–40,000 IU of vitamin D 3 once a week, with a daily maintenance dosage of 4,000–6,000 IU/day on the remaining 6 days, has shown efficiency in improving the vitamin D level of 3 patients with intestinal failure. A prospective study with 40 infants and toddlers in Qatar reported that parenteral injection of a megadose (10,000 IU/kg) of vitamin D3 for 3 months normalized all the laboratory findings and radiological manifestations [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations